More answers

c+(-8)= -20

c - 8 = -20 (positive add negative just equals a negative)

c = -20 + 8 (8 is brought to other side and made positive)

Therefore, c = -12

Q: What is the answer to c plus -8 equals -20?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

c plus 8 equals 11; now subtract 8 from both sides, then c=3.

a = 20 b = 60 c = 100

2c+(12-4)=20 Simplify the expression in the parentheses first. 2c+8=20 Subtract 8 from both sides of the equation. 2c=12 Divide both sides of the equation by 2. c=6

144 Formula: c= (a2)+(ab)

It is an equation and the value of c works out as 8

Related questions

c plus 8 equals 11; now subtract 8 from both sides, then c=3.

a = 20 b = 60 c = 100

A=8 B=4 C=14 Yes, I know I'm a genius. Mak - the all knowing one. MWAHAHAH!

a+b+c+d+e = 30 (i) c+e = 14 (ii) d+b = 1 (iii) a = 2b-1 (iv) a+c = 10 (v) By (i)-(ii)-(iii): a = 15 then, by (iv): b = 8 and by (v): c = -5 Also, b = 8 so by (iii): d = -7 and then by (i), e = 19

the answer is a

a + b + c = 180 b = 3a c = 5a Substituting the values of b and c into the first equation. a + 3a + 5a = 180 or 9a = 180 so that a = 20 then b = 3a = 3*20 = 60 and c = 5a = 5*20 = 100

2c + 4 - 3c = -9 + c + 5 -c + 4 = c - 4 -2c = -8 2c = 8 c = 4

4

2c+(12-4)=20 Simplify the expression in the parentheses first. 2c+8=20 Subtract 8 from both sides of the equation. 2c=12 Divide both sides of the equation by 2. c=6

144 Formula: c= (a2)+(ab)

It is an equation and the value of c works out as 8

2a + 2b = 26 2b + c = 22 ===> b = 11 - c/2 4c + 2b = 46 ===> b = 23 - 2c From the 2nd and 3rd equations: 11 - c/2 = 23 - 2c 22 - c = 46 - 4c 22 - 46 = -4c + c ===> -24 = -3c ===> c = 8 Substitute c=8 into the 3rd equation: b = 23 - 16 = 7 Substitute b=7 into the 1st equation: 2a + 14 = 26 2a = 12 ===> a = 6